Visual words in notes English language SDN Layungsari 2 Bogor City - Alya, Nurma; Helmanto, Fachri; Rajagukguk, Zahra Fitrah (LADU: Journal of Languages and Education, 2024)
Background: Write is activity combine later letters​​​ formed become a word that has . Results obtained from activity write namely writing. In writing our writing need notice something rule about how method good writing​ ie with orthography. In English language, introduction or wording will​ become complicated because need ability To use compile something letters to become a piece of writing that can understood and comprehended by the reader. However in fact there is various type visual form of words on notes English language student school base layungsari 2 cities Bogor. Every student own character letter or the visual character of the writing is different, still Lots students who haven't use letter capital at the beginning of the text and still lots students who use letter capital in the middle of the word. As for the fallacy in writing form letters, there are a number of letter which similar with letter . Purpose: Research This is for knowing visual words in written English language student sdn layungsari 2 bogor city and expected can become reference learning about with visual words in writing Design and methods: Types of research This use qualitative with technique analysis fill in 60 student writings and use triangulation as data validity . Results: Yes visual diversity of words in notes language English Layungsari State Elementary School 2 cities Bogor. Happens often​ similarity in writing which letters can be changing the meaning of a word and of course can confusing and difficult reader as in the similar letter e letter c, letter a without hat (a) similar with letter o and letter letter a without hat (a) similar with letter q p the Because a number of factors, such as lack of trust self in writing every the letters are, lacking knowledge to something letter or the word will written as well as factor deliberate.